The killifish germline regulates longevity and somatic repair in a sex-specific manner - Moses, Eitan; Atlan, Tehila; Sun, Xue; Franěk, Roman; Siddiqui, Atif; Marinov, Georgi K; Shifman, Sagiv; Zucker, David M; Oron-Gottesman, Adi; Greenleaf, William J; Cohen, Ehud; Ram, Oren; et al. (Nature aging, 2024)
Classical evolutionary theories propose tradeoffs among reproduction, damage repair and lifespan. However, the specific role of the germline in shaping vertebrate aging remains largely unknown. In this study, we used the turquoise killifish (Nothobranchius furzeri) to genetically arrest germline development at discrete stages and examine how different modes of infertility impact life history. We first constructed a comprehensive single-cell gonadal atlas, providing cell-type-specific markers for downstream phenotypic analysis. We show here that germline depletion-but not arresting germline differentiation-enhances damage repair in female killifish. Conversely, germline-depleted males instead showed an extension in lifespan and rejuvenated metabolic functions. Through further transcriptomic analysis, we highlight enrichment of pro-longevity pathways and genes in germline-depleted male killifish and demonstrate functional conservation of how these factors may regulate longevity in germline-depleted Caenorhabditis elegans. Our results, therefore, demonstrate that different germline manipulation paradigms can yield pronounced sexually dimorphic phenotypes, implying alternative responses to classical evolutionary tradeoffs.
Keywords: Caenorhabditis elegans; Germ Cells; pohlavní dimorfismus; Longevity; Female; Animals; ženské pohlaví; Sex Characteristics; mužské pohlaví; Male; zvířata; zárodečné buňky; dlouhověkost